Learning Eclipse Java IDE - Gorman, Brian (InfiniteSkills, 2014)
"In this Eclipse Java IDE training course, expert author Brian Gorman teaches you how to develop applications in this integrated development environment. This course assumes you have some knowledge of Java. You will start by learning how to create a project, including creating packages and classes, running the program, and the project folder structure. Brian will then teach you advanced project operations and editor and general shortcuts. This video tutorial will cover the file and edit menus, the source, refactoring, and navigating and searching. Finally, you will learn how to build and run projects, including running and debugging the project and setting breakpoints, watchers, and stepping through code. Once you have completed this computer based training course, you will have gained the knowledge necessary to develop your own applications in Eclipse. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.